The Effect of Social Factors on the Performance Levels of Project - Dissanayake, D.M.R; Wanninayake, W.M.C.B. (Gyan Management Journal, 2010)
Sri Lanka has been positive on service sector and industrial sector development as per the government , : : "Omic policies implemented,. Both local and foreign companies have been operating at highest scale industries where the clients are mostly government and private investors in different : , ::.s like hotels, banks and manufacturers. However, there are critical events where it has been found : : • Jf productivity at project completion stage due to both human and technical matters. Therefore, :- .· ,
Keywords: project management; construction industry; project performance; social factors